The Role of Infrastructure Investment Location in China's Western Development - Luo, Xubei (The World Bank, 2004)
Development of the western region is vital to the balanced growth of China. Luo studies the impacts of infrastructure investment that may most efficiently alleviate the burden of geographical remoteness of the West. Having constructed the "adjusted distance" to approximate the transport cost, which takes into account the effects of real distance and infrastructure development, the author defines the "peripheral degree" to measure the effective remoteness of a province to an economic center. Using panel data for 1979–99 from the Chinese provinces, she shows that geographic attractiveness plays a significant role in a Solow-type growth determination model. Given the invariability of pure geographic position, progress in transportation facilities is essential to reduce the geographic handicap and to encourage the catching-up of the western region. The author's simulation results show that the central transportation hubs (Hubei, Henan, and Hunan) merit most infrastructure investments, for they favor the development of many provinces, if regional balanced growth is considered as the prime objective. In particular, improvement in the transportation facilities in central hubs will have greater effects on western development than that in the western region by itself. Improvements in the transportation facilities of the central hubs substantially improves the geographic attractiveness of the western region by reducing the transport cost from the West to the Coast and by promoting the emergence of new economic centers in such hubs, which tends to modify the national economic geographic structure. This paper is a product of the Office of the Vice President and Chief Economist, Development Economics